The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.5120/3362-4641
|View full text |Cite
|
Sign up to set email alerts
|

A Smart Algorithm for Dynamic Task Allocation for Distributed Processing Environment

Abstract: A Distributed Processing Environment (DPE) consists of multiple autonomous computers that communicate through a communication media. In DPE a task is divided into many fractions and each of which is to be get processed. The task allocation problem can be explained in terms of number of tasks and number of processors available. In the present method propose a dynamic model for task allocation in DPE. Present method describes the allocation of m tasks in the environment of distributed processing with n processor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
(16 reference statements)
0
7
0
Order By: Relevance
“…The communication cost of the tasks in the same cluster is assumed to be zero. Using this strategy it has been observed that the total system cost is less as compared to that which is obtained by the heuristic reported in [5].…”
Section: Cluster-based Schedulingmentioning
confidence: 93%
See 2 more Smart Citations
“…The communication cost of the tasks in the same cluster is assumed to be zero. Using this strategy it has been observed that the total system cost is less as compared to that which is obtained by the heuristic reported in [5].…”
Section: Cluster-based Schedulingmentioning
confidence: 93%
“…Now, the ACL(,) and SUMNEW(,) are: Step 8: COST(,) = FIN(,). On applying Hungarian Algorithm [5] to the FIN (,). We get 0 1 0 ALLOC(,) = 0 0 1 1 0 0…”
Section: Implementation Of Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…For this master problem, two main directions of finding solutions are suggested, either classifying solutions from a best non-dominated level, or projecting the solutions to a created dimension so as to have a comparable objective function. Aligning to the former suggestion, Chaharsooghi et al enhanced the ant colony optimization algorithm to figure out an allocation (Chaharsooghi, 2008), and Govil considered the cost of re-allocation as the objective to be optimized (Govil, 2011). Since the design problem in the operation stage limits the number of plan possibilities, it makes the constraints more stringent than common NP-hard problems.…”
Section: Decision-making In Multi-objective Questionmentioning
confidence: 99%
“…There is several task allocation methods like load balancing, integer programming, divide and conquer, grid computing [1] are reported in literature for distributed production and distributed systems and specifically for GSD techniques in literature are modification request [2], global studio Project [3], distributed Cocomo [4], Simulation model [5], Reference model for GSD [6], 24 hour software development model [7], TAMARI [8]. Still there is a need for appropriate and efficient work load sharing strategies to improve the performance of GSD teams.…”
Section: Introductionmentioning
confidence: 99%